2019
DOI: 10.2147/ccid.s206115
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association between heterozygote Val92Met <em>MC1R</em> gene polymorphisms with incidence of melasma: a study of Javanese women population in Yogyakarta</p>

Abstract: Introduction: Melasma is an acquired hypermelanosis of the face. The pathogenesis of melasma is multifactorial and may be caused by interactions between genetics and the environment. Research has shown that skin pigmentation is regulated by the Melanocortin-1 Receptor gene ( MC1R ). In Japanese populations, Val92Met and Arg163Gln genotypes of MC1R gene polymorphisms are associated with freckles and lentigo solaris, because they have skin types II–III, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…The study found that all races have the risk of Melasma, but Asian, Indian, Latin American, and African Americans have a higher prevalence [3][4]. A recent genetic analysis of a cohort study found a significant correlation between the occurrence of Melasma and race, family history, and genetic factors, with more than 64% of patients having a positive family history [5]. The study of 56 patients with Melasma, and 39 healthy controls in the White Dynasty showed that the incidence of Melasma was related to the polymorphism of ERα gene Xba I genotype, ERβ gene Alu I, and Rsa I genotype.…”
Section: Genetics and Melasmamentioning
confidence: 97%
“…The study found that all races have the risk of Melasma, but Asian, Indian, Latin American, and African Americans have a higher prevalence [3][4]. A recent genetic analysis of a cohort study found a significant correlation between the occurrence of Melasma and race, family history, and genetic factors, with more than 64% of patients having a positive family history [5]. The study of 56 patients with Melasma, and 39 healthy controls in the White Dynasty showed that the incidence of Melasma was related to the polymorphism of ERα gene Xba I genotype, ERβ gene Alu I, and Rsa I genotype.…”
Section: Genetics and Melasmamentioning
confidence: 97%
“…The most potent regulator of eumelanogenesis is the melanocortin type 1 receptor (MC1R), which is transcripted from a highly polymorphic gene responsible for multiple phenotypes of skin and hair color, as well as skin sensitivity to ultraviolet radiation [ 14 ]. In melasma, MC1R polymorphism, as characterized by substitution of guanosine for adenosine at codon 92 (Val92Met), is prevalent in Javanese women when compared with controls [ 15 ].…”
Section: Geneticsmentioning
confidence: 99%
“…Broad-spectrum sunscreen (SPF 30) application was shown to reduce nevi in children in a 2000 study (Young et al, 2017). The incidence of melasma often occurs in Indonesia, because the majority of population has Fitzpatrick IV skin type (Suryaningsih et al, 2019). Based on the description above, authors are interested in conducting research on "The Relationship between Sunscreen Application and Severity of Melasma".…”
Section: Introductionmentioning
confidence: 99%